Poly-Lysine-Derived Carbon Quantum Dots Promote the Repair of Bone Defects in Osteomyelitis Through Antibacterial and Osteogenic Effects - Wu J; Yan H; Yang X; Qiao L; Rao X; Zhou R (International Journal of Nanomedicine)
Jianghong Wu,1,2,* He Yan,1,* Xiaorong Yang,1 Li Qiao,1 Xiancai Rao,2 Renjie Zhou1 1Department of Emergency, The Second Affiliated Hospital, Army Medical University, Chongqing, People’s Republic of China; 2Department of Microbiology, College of Basic Medical Science, Army Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiancai Rao, Department of Microbiology, College of Basic Medical Science, Army Medical University, Chongqing, 400037, People’s Republic of China, Email xcrao@tmmu.edu.cn Renjie Zhou, Department of Emergency, The Second Affiliated Hospital, Army Medical University, Chongqing, 400037, People’s Republic of China, Email zhourenjie@tmmu.edu.cnBackground: Osteomyelitis is a challenging clinical condition to manage effectively. In this study, we used ϵ-Poly (L-lysine) as the raw material to synthesize carbon quantum dots (PL-CQDs). These PL-CQDs possess antibacterial and osteogenesis ability, and are expected to improve the therapeutic effect of osteomyelitis.Methods: PL-CQDs were synthesized via a dry heat-intermittent ultrasound method and characterized. The antibacterial efficacy of PL-CQDs was assessed using the spread plate method. The biological functions of PL-CQDs were evaluated through CCK-8 assays, scratch wound healing assay, osteogenic differentiation experiments, and transcriptome sequencing. In the in vivo experiments, the rats with osteomyelitis were evenly divided into five groups and treated with calcium sulfate containing different concentrations of PL-CQDs, and the therapeutic effects were evaluated by micro-CT and histology.Results: PL-CQDs at concentrations of 200, 400, and 800 μg/mL exhibited no cytotoxicity and demonstrated the ability to kill methicillin-resistant Staphylococcus aureus and Escherichia coli. Additionally, PL-CQDs promoted the migration and osteogenic differentiation of mouse pre-osteoblasts (MC3T3-E1) cells. Transcriptome sequencing revealed that PL-CQDs significantly altered the ECM-receptor interaction signaling pathways and participated in biological processes such as the positive regulation of chondrocyte proliferation, collagen fiber organization, and regulation of fibroblast proliferation. Micro-CT and Masson staining results showed that the incorporation of PL-CQDs at different concentrations was beneficial to the repair of osteomyelitis defects, with the best repair in the PL-CQD50@CS group. Immunohistochemistry (CD31, DMP1) suggested that PL-CQDs facilitated the repair of osteomyelitis by enhancing matrix deposition and vascularization at the bone defect site.Conclusion: PL-CQDs exhibit antibacterial and osteogenic properties and may serve as a potential alternative treatment for osteomyelitis.Keywords: carbon quantum dots, osteomyelitis, extracellular matrix deposition